Effectiveness and complications of primary C-clamp stabilization or external fixation for unstable pelvic fractures. Issue 11 (November 2019) - Schmal, Hagen; Larsen, Morten Schultz; Stuby, Fabian; Strohm, Peter C.; Reising, Kilian; Goodwin Burri, Kelly
Highlights: Initial use of C-clamp or external fixation for unstable pelvic fractures is associated with a decreased mortality. These emergency measures are not an independent risk factor for complications after secondary surgery. The risk for infection after ilio-sacral screw fixation was almost 5-fold increased when primarily a C-clamp was used. In conclusion, emergency stabilization of pelvic fractures is a safe procedure which potentially can save lives. However, the risk for ilio-sacral screw implantation after C-clamp use should be evaluated cautiously. Abstract: Background and purpose: Unstable pelvic fractures frequently require emergency stabilization using a C-clamp or external (CC/EF) fixation. However, the effectiveness of this intervention and associated complications are still a matter of debate. Patients and methods: The analysis used data available from the German Pelvic Trauma Registry to study general complications, infections and mortality after primary stabilization using CC/EF in 5, 499 patients (n = 957 with vs n = 4, 542 without). Furthermore, the subgroups with secondary surgery (n = 713 vs n = 1, 695), and ilio-sacral screw implantation following C-clamp stabilization were evaluated (n = 24 vs n = 219). Calculated odds ratios were adjusted for potential confounders. Results: Patients treated by CC/EF were younger (45 ± 20 vs 62 ± 24 years), had more C-type fractures (65% vs 28%), higher ISS (≥25 63% vs 20%) and displacement (≥3 mm 81% vs 41%), and more complex fractures (32% vs 5%). These features were independent risk factors for complications (p < 0.001). While mortality was reduced after CC/EF stabilization by 32% (OR 0.68 95%CI 0.49-0.95), the risk for general complications was slightly increased (OR 1.25 95% CI 1.02–1.53). In patients undergoing secondary surgery, CC/EF fixation had no influence on mortality, general complications or infections. Related to preceding C-clamp stabilization (OR 4.67 95% CI 1.06–20.64), the risk for infection increased from 3.2% to 20.8% in ilio-sacral screw fixation. Interpretation: Primary stabilization of unstable pelvic fractures with C-clamp or external fixation is associated with a decreased mortality and was not an independent risk factor for complications after secondary surgery. However, the risk for infection after ilio-sacral screw fixation increased almost 5-fold after C-clamp use.